2016
DOI: 10.1371/journal.pone.0151579
|View full text |Cite|
|
Sign up to set email alerts
|

Paternal B Vitamin Intake Is a Determinant of Growth, Hepatic Lipid Metabolism and Intestinal Tumor Volume in Female Apc1638N Mouse Offspring

Abstract: BackgroundThe importance of maternal nutrition to offspring health and risk of disease is well established. Emerging evidence suggests paternal diet may affect offspring health as well.ObjectiveIn the current study we sought to determine whether modulating pre-conception paternal B vitamin intake alters intestinal tumor formation in offspring. Additionally, we sought to identify potential mechanisms for the observed weight differential among offspring by profiling hepatic gene expression and lipid content.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…A single study comparing paternal B vitamin supplementation, repletion and depletion has been conducted in the Apc1638N model in which the endpoint of offspring intestinal tumorigenesis was examined. No overt changes in tumor incidence or multiplicity were observed although mean tumor volume increased in the female offspring in a stepwise fashion with increasing paternal B vitamin intake (Sabet et al, 2016).…”
Section: Might Maternal Folate Consumption Impact On Cancer Risk In Omentioning
confidence: 80%
“…A single study comparing paternal B vitamin supplementation, repletion and depletion has been conducted in the Apc1638N model in which the endpoint of offspring intestinal tumorigenesis was examined. No overt changes in tumor incidence or multiplicity were observed although mean tumor volume increased in the female offspring in a stepwise fashion with increasing paternal B vitamin intake (Sabet et al, 2016).…”
Section: Might Maternal Folate Consumption Impact On Cancer Risk In Omentioning
confidence: 80%
“…Environmental factors exert significant effects on gene expression, in some instances through epigenetic mechanisms ( 14 ). Thus, epigenetic marks can be considered “fingerprints” of that communication between the environment and the genome and some experimental evidence indicates that diet-induced epigenetic changes can be transmitted through several generations ( 15 , 16 ). As such, the environment, including habitual diet, may contribute to the health status of the individual and his/her descendants ( 17 ).…”
mentioning
confidence: 99%
“…Hepatic transcriptome analyses suggested a disruption of lipid metabolism and subsequent analyses revealed that despite being lighter, female offspring of supplemented sires had an approximately three-fold elevation in hepatic triglyceride content. Sex-specific re-analysis of our RNA-seq data revealed a significant upregulation of three genes (Acaca, Elovl6, Gpam), the products of which are sequentially involved in de novo triglyceride synthesis in the liver (Sabet et al 2016). Thus these data also suggest that paternal on-carbon status may also be a determinant of offspring metabolism, and raise the intriguing possibility of an interaction of maternal and paternal diet in programming offspring health.…”
Section: Paternalmentioning
confidence: 56%
“…Given the constant production of sperm through adult life, the integrity of the genetic and epigenetic information carried within is constantly at the mercy of an adequate nutrient supply. Indeed, we (Sabet et al 2016) and others (Lambrot et al 2013) have recently demonstrated that altering paternal B vitamin intake can cause widespread changes in the sperm methylome. It remains to be seen which, if any, of these methylation changes escape the widespread demethylation that occurs during embryogenesis -a task that will require single base resolution comparisons of sperm and offspring methylomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 82%